From Légère Teinture to Central Place: A Revaluation of Book and Library History Within Library and Information Science Programmes. - Delsaerdt, Pierre (Library History, 2008)
The author demonstrates that book and library history deserves a central place in library and information science programmes, but also that in order to obtain or keep this central place it needs to orient itself in a direction that is closer to the heart of what library and information science is about – the organization of knowledge and information-seeking behaviour. Book and library history can illustrate these processes and explain how they have developed in the past. Early phenomena of knowledge organization have to be studied in their broader contexts, and these contexts to a large extent cover the production, dissemination and consumption of books in the past. The main return that book history will get out of this process is that it will be more strongly integrated into academic teaching and research.